Stainless steel material containing Al2O3 coating and preparation method thereof
Al2O3 coating was prepared on the surface of the stainless steel matrix by electrophoretic deposition and high-temperature oxidation. Combined with the close combination of the transition layer and the alumina layer, the corrosion, high-temperature oxidation and wear of stainless steel materials in harsh environments is solved, and the material's oxidation resistance, hardness and wear resistance are significantly improved.
Patent Information
- Application Number
- CN202510360739.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
In the prior art, stainless steel materials face problems such as corrosion, high temperature oxidation and wear in harsh working environments, and common aluminum plating methods have defects such as high equipment requirements and unstable performance.
The Al2O3 coating was prepared on the surface of the stainless steel matrix by electrophoretic deposition and aluminum plating-high temperature oxidation. The interfacial bonding force was improved through the close bonding of the transition layer and the alumina layer, and the Al atoms in the alumina layer were diffused to the matrix through heat treatment and high-temperature oxidation, forming a transition layer containing the FeAl phase and Fe2Al5 phase.
It significantly improves the oxidation resistance, hardness and wear resistance of stainless steel materials. It is suitable for stainless steel workpieces with complex structures. It has simple process, strong controllability and environmentally friendly.
Smart Images

Figure CN119877062A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a stainless steel material containing Al2O3 coating and a preparation method thereof, and in particular to a method for preparing Al2O3 coating on the surface of a stainless steel substrate by using an electrophoretic deposition aluminum plating-high temperature oxidation method, belonging to the field of ceramic material preparation. Background Art
[0002] Stainless steel has good welding performance, plasticity and toughness, and can maintain high strength at high temperatures, so it is widely used in the fields of shipbuilding, chemical industry and machinery manufacturing. With the rapid development of industry, the working environment faced by stainless steel workpieces has become increasingly harsh, and the requirements for its material resistance to thermal shock, wear, fatigue, high temperature and corrosion have also increased. In many fields, the corrosion, high temperature oxidation and wear problems of equipment have become more and more serious.
[0003] After aluminum plating on the surface of stainless steel, a layer of Al2O3 film will naturally form on the surface of the coating, which greatly improves its corrosion resistance and high-temperature oxidation resistance. However, the Al2O3 film naturally formed on the surface of the aluminum coating in the atmosphere is very thin, with a thickness of only a few nanometers. In order to meet higher performance requirements, high-temperature oxidation is often used in industry to prepare Al2O3 coatings. Currently, the commonly used aluminum plating methods include chemical vapor deposition, hot-dip aluminum plating, electrophoretic deposition aluminum plating, powder embedding aluminum plating and molten salt electroplating aluminum plating. Among them, chemical vapor deposition has high equipment requirements and high preparation temperature, which will have a greater impact on the stainless steel substrate. Hot-dip aluminum plating is also carried out at high temperatures, and holes and peeling are prone to appear on the surface of the aluminum coating, which not only makes the aluminum layer loose, but also seriously affects the oxidation resistance and corrosion resistance of the aluminum layer. The dust in powder embedding aluminum plating seriously pollutes the environment and is harmful to the human body. The amount of aluminizing agent used is relatively large, and each aluminum plating consumes 10%~20% of the aluminum source, which is mainly caused by oxidation, so new aluminum material should be added when using old materials. Molten salt electroplating of aluminum can obtain a smooth, continuous, and uniformly thick aluminum coating at a relatively low temperature, but the aluminum coating prepared by this method is relatively thin and it is difficult to achieve a large thickness.
[0004] Electrophoretic deposition technology is a relatively new method for preparing ceramic materials and thin films, which has received widespread attention in recent years. Electrophoretic deposition aluminum plating is carried out at room temperature and requires simple equipment, which is suitable for large-scale industrial production. At the same time, it has a short molding time and low requirements on the substrate shape, and aluminum can be plated on special-shaped parts with complex structures. If electrophoretic deposition technology can be introduced into the preparation of stainless steel material coatings, it is expected to further improve the comprehensive performance of stainless steel workpieces. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the first purpose of the present invention is to provide a stainless steel material containing an Al2O3 coating, in which the stainless steel substrate is tightly bonded to the alumina layer through a transition layer, and the boundary is neat and crack-free. At the same time, a metallurgical bond is generated between the transition layer and the substrate, which can greatly improve the interfacial bonding strength between the alumina layer and the substrate, and enhance the oxidation resistance, hardness and wear resistance of the stainless steel material.
[0006] The second object of the present invention is to provide a method for preparing a stainless steel material containing an Al2O3 coating. The method prepares an aluminum oxide coating by synergistically preparing an aluminum oxide coating through an electrophoretic deposition aluminum plating-high temperature oxidation method, and utilizes a heat treatment and high temperature oxidation process to allow Al atoms in the aluminum oxide layer to diffuse into a substrate to form a transition layer containing a FeAl phase and a Fe2Al5 phase, thereby improving the interfacial bonding strength of the material. The method is applicable to various stainless steel workpieces with complex structures; and the use of a special deposition liquid and heat treatment can ensure the uniformity and integrity of the coating, thereby ensuring the anti-oxidation performance and mechanical properties of the coating.
[0007] In order to achieve the above technical objectives, the present invention provides a stainless steel material containing an Al2O3 coating, comprising a stainless steel substrate, a transition layer and an aluminum oxide layer, wherein the stainless steel substrate and the aluminum oxide layer are connected via the transition layer; the transition layer comprises a FeAl phase and a Fe2Al5 phase; the aluminum oxide layer comprises an α-Al2O3 phase and a γ-Al2O3 phase, and the content of the α-Al2O3 phase is greater than that of the γ-Al2O3 phase; and the thickness ratio of the aluminum oxide layer to the transition layer is (1~5):(2~7).
[0008] In the stainless steel material of the present invention, the stainless steel substrate is tightly combined with the alumina layer through the transition layer, and the boundary is neat and crack-free. At the same time, the metallurgical bonding between the transition layer and the substrate can greatly improve the interface bonding force between the alumina layer and the substrate. In addition, the phase structure in the transition layer and the alumina layer has an important influence on the performance improvement of the stainless steel material. Specifically, the α-Al2O3 phase and the γ-Al2O3 phase in the alumina layer of the present invention both have high hardness, and the mixed coating can significantly improve the hardness of the surface of the stainless steel material, making it more resistant to wear, friction and mechanical impact, and extending the service life in a high wear environment. However, the single α-Al2O3 phase coating is relatively brittle, while the γ-Al2O3 has relatively better toughness and bonding force with the substrate. The coating formed by the mixture of the two can have both certain toughness and high hardness, can withstand a certain degree of deformation without breaking, and can firmly adhere to the stainless steel substrate, is not easy to peel off, and improves the reliability and stability of the coating. In addition, the thermal expansion coefficients of the stainless steel substrate and alumina ceramics are quite different, which will generate large thermal stress when the temperature changes, while the thermal expansion coefficients of the FeAl phase and the Fe2Al5 phase are between those of stainless steel and alumina ceramics. As a transition layer, they can play a transitional role between the two, making the thermal expansion process more coordinated and reducing the thermal stress caused by thermal expansion mismatch. At the same time, during the heat treatment and high-temperature oxidation process, due to atomic diffusion, the side close to the stainless steel substrate is more likely to form the FeAl phase, and the side close to the alumina coating is more likely to form a transition layer structure of the Fe2Al5 phase. This distribution combines the FeAl phase and the Fe2Al5 phase with certain elasticity and plasticity, which can absorb and buffer thermal stress to a certain extent. When the temperature changes, the transition layer can adapt to the thermal expansion or contraction of stainless steel and ceramics through its own deformation, thereby reducing the thermal stress concentration at the interface and improving the stability and reliability of the composite material under temperature cycling conditions. Finally, the FeAl phase and the Fe2Al5 phase can be interlocked with the microstructure of the stainless steel substrate and the alumina ceramic surface, increasing the roughness and contact area of the interface, thereby improving the mechanical bonding between the two and making the entire composite material more stable.
[0009] And through experiments, it is found that when the content of α-Al2O3 phase is greater than that of γ-Al2O3 phase, the hardness and wear resistance of the material can be further improved while slightly sacrificing the anti-oxidation performance of the stainless steel material. At the same time, the thickness ratio can be changed by adjusting the heat treatment time. The longer the heat treatment time, the thicker the transition layer. The thicker the transition layer, the stronger the ability to resist thermal shock, and the thicker the alumina coating, the stronger the resistance to high-temperature oxidation.
[0010] As a preferred solution, the stainless steel matrix contains Fe and at least one of Cr, Ni, Mo, Mn and Ti. The Fe element in the stainless steel matrix mainly combines with Al atoms to form an iron-aluminum alloy phase when diffusing into the matrix, and when other reinforcing phase metal elements are present in the matrix, the corrosion resistance of the material can also be improved.
[0011] The present invention also provides a method for preparing a stainless steel material containing an Al2O3 coating, which comprises the steps of electrophoretic deposition of aluminum on the surface of a stainless steel substrate to deposit a powdered aluminum coating, then heat treating the aluminum powder layer in an inert gas to form a molten state, and then subjecting the aluminum powder layer to high-temperature oxidation to obtain the obtained material; the deposition liquid used for the electrophoretic deposition of aluminum comprises metallic aluminum powder, polyvinyl butyral, aluminum nitrate and / or aluminum nitrate hydrate and anhydrous ethanol.
[0012] The key to the technical solution of the present invention is to first use electrophoretic deposition to provide a large driving force to uniformly deposit polyvinyl butyral containing aluminum powder in the deposition liquid onto the surface of stainless steel, and then perform heat treatment and high-temperature oxidation in an inert gas to allow aluminum atoms to diffuse into the substrate through a vacancy mechanism to simultaneously obtain an intermediate transition layer and an Al2O3 coating.
[0013] Unlike the traditional electrophoretic deposition solution that uses aluminum sol to directly deposit and form an aluminum oxide coating, the electrophoretic deposition solution of the present invention must use metal aluminum powder to simultaneously form a transition layer and an aluminum oxide layer during heat treatment and high-temperature oxidation, significantly improving the bonding strength between the aluminum oxide layer and the substrate layer. However, when using metal aluminum powder, unlike aluminum sol, on the one hand, the deposition solution does not contain solvent water, resulting in poor conductivity of the deposition solution, and electrophoretic deposition cannot be effectively achieved. On the other hand, aluminum powder has poor dispersibility in anhydrous ethanol. Therefore, the present invention adds polyvinyl butyral (PVB) to the electrophoretic deposition solution to provide steric stabilization and reduce the viscosity of the suspension, effectively improving the stability and dispersibility of the suspension, and adding aluminum nitrate to improve the conductivity of the deposition solution. However, PVB will entrain aluminum powder, and it also contains anhydrous ethanol solvent. Since the hydroxyl hydrogen atoms of ethanol are very active and weakly acidic, and polyvinyl butyral also contains hydroxyl groups that are easy to form hydrogen bonds, it will adsorb the partially ionized H + , which causes the PVB containing aluminum powder to be positively charged, undergo electrophoretic migration, and deposit at the cathode. +The electrons at the cathode generate hydrogen. In addition, electrophoretic deposition is accompanied by the occurrence of electrolyzed water. Both of these situations will have an adverse effect on deposition, causing the uniformity and firmness of the coating to deteriorate. Experiments have found that after electrophoretic deposition and drying, a uniform aluminum coating is formed on the stainless steel substrate. However, at this time, the aluminum coating is a powder layer, and its bonding with the substrate is only physical bonding, and the bonding force is weak. Since the aluminum coating after electrophoretic deposition is a powder layer, if it is directly oxidized to form an aluminum oxide coating, the aluminum oxide coating will eventually break. However, in the present invention, before the aluminum coating is oxidized, the aluminum powder is melted by heat treatment, so that the aluminum coating becomes uniform and dense, and further forms a metallurgical bond with the substrate after high-temperature oxidation.
[0014] As a preferred solution, the stainless steel substrate is 316L stainless steel. Compared with other grades of stainless steel, 316L stainless steel has a higher nickel content and an additional 2% of molybdenum, and has stronger corrosion resistance.
[0015] As a preferred solution, the stainless steel substrate is first polished step by step with silicon carbide sandpaper before electrophoretic deposition, and then ultrasonically cleaned with anhydrous ethanol and acetone in sequence.
[0016] As a preferred solution, the deposition liquid is prepared by adding aluminum nitrate and / or aluminum nitrate hydrate, metal aluminum powder and a binder to anhydrous ethanol in proportion in sequence while maintaining magnetic stirring, and then performing magnetic stirring and ultrasonic dispersion to obtain an electrophoretic deposition liquid.
[0017] As a preferred solution, the content of metal aluminum powder in the deposition liquid is 80-120 g / L, the content of polyvinyl butyral is 10-45 g / L, and the content of aluminum nitrate and / or aluminum nitrate hydrate is 60-140 g / L in terms of aluminum nitrate.
[0018] The amount of polyvinyl butyral, metal aluminum powder and aluminum nitrate powder added in the present invention has a direct impact on the deposition effect. Polyvinyl butyral plays an important role in achieving the adhesion of the sediment, preventing cracks and improving the stability of the suspension during electrophoretic deposition. However, when the content of polyvinyl butyral added to the deposition liquid is too high, the viscosity of the deposition liquid will be too large, which is not conducive to the occurrence of electrophoretic deposition. It is further preferred that the content of polyvinyl butyral in the deposition liquid is 35-40 g / L.
[0019] Increasing the amount of aluminum powder added appropriately can increase the concentration of aluminum powder suspended in the deposition liquid, thereby increasing the amount of aluminum coating deposited. However, excessive aluminum powder will make the electrophoretic deposition liquid unstable and difficult to maintain in a suspended state. After standing, the aluminum powder will accumulate at the bottom of the deposition liquid and even precipitate, which is obviously not conducive to the occurrence of electrophoretic deposition. It is further preferred that the aluminum powder content in the deposition liquid is 90-100 g / L.
[0020] The content of aluminum nitrate directly affects the conductivity of the electrophoretic deposition solution. When the conductivity of the electrophoretic deposition solution is at a low level, the conductivity of the electrophoretic deposition solution is poor and precipitation is easy to occur. And the conductivity also has a great influence on the deposition current during the deposition process. The greater the conductivity, the greater the deposition current, and the deposition rate will also increase accordingly. However, when the conductivity exceeds a certain value, the excessive deposition current will cause a large number of bubbles to be generated on the cathode, which is not conducive to the formation of the aluminum coating, and will also destroy the uniformity of the aluminum coating, causing the deposition amount to decrease. Secondly, the excessive deposition current will also cause the temperature of the electrophoretic deposition solution to rise rapidly, seriously affecting the formation of the aluminum coating. It is further preferred that the aluminum nitrate content in the deposition solution is 100~120g / L.
[0021] As a preferred solution, the conditions for electrophoretic deposition aluminum plating are: a stainless steel substrate is used as a negative electrode, graphite is used as a positive electrode, a deposition voltage is 80-120V, and a deposition time is 5-10min. The deposition voltage is an important process parameter in the electrophoretic deposition method. The magnitude of the deposition voltage affects the strength of the constant voltage electric field in the deposition liquid, and further affects the driving force exerted on the charged particles. In the present invention, since the deposition liquid does not contain a conductive solvent, its conductivity is relatively low, and thus the deposition voltage range used is relatively large.
[0022] As a preferred solution, the heat treatment condition is: in an argon atmosphere, the temperature is raised to 700-800°C at a rate of 5-10°C / min and kept at that temperature for 1-3 hours. A further preferred temperature is 700-750°C.
[0023] As a preferred solution, the high temperature oxidation condition is: heating to 900-1050°C at 1-5°C / min in an oxidizing atmosphere, keeping the temperature for 5-25h, and then cooling to room temperature with the furnace. The oxidizing atmosphere used in the present invention includes air, oxygen, etc. It is further preferred to heat to 900-950°C, and the high temperature oxidation time is 15-20h.
[0024] The temperature range of the heat treatment and high temperature oxidation of the present invention is mainly based on the phase structure composition of the transition layer and the aluminum oxide layer. When the heat treatment temperature reaches 700°C, Al atoms will diffuse into the matrix to generate FeAl phase and Fe2Al5 phase, but above 800°C, part of the Fe2Al5 phase will transform into the FeAl phase. At about 900°C, the γ-Al2O3 phase can begin to transform into the α-Al2O3 phase, and as time or temperature increases, more and more γ-Al2O3 phases begin to transform into α-Al2O3 phases.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The electrophoretic deposition aluminum plating-heat treatment-high temperature oxidation method of the present invention is applicable to various stainless steel components with complex structures and has good bonding with the substrate.
[0027] (2) The present invention can prepare a coating on a stainless steel substrate by controlling the parameters of electrophoretic deposition. At the same time, the electrophoretic deposition time and voltage can also be changed to obtain coatings of different thicknesses. The process is simple and highly controllable.
[0028] (3) The stainless steel material provided by the present invention has a substrate that is tightly bonded to the alumina layer through a transition layer with a neat boundary without cracks. At the same time, a metallurgical bond is generated between the transition layer and the substrate, which can greatly improve the interfacial bonding strength between the alumina layer and the substrate, and enhance the oxidation resistance, hardness and wear resistance of the stainless steel material.
[0029] (4) The preparation method of the present invention utilizes the process of heat treatment and high-temperature oxidation to diffuse the Al atoms in the alumina layer into the substrate to form a transition layer containing the FeAl phase and the Fe2Al5 phase, thereby improving the interfacial bonding strength of the material. The use of a special deposition liquid and heat treatment can ensure the uniformity and integrity of the coating, thereby ensuring the oxidation resistance and mechanical properties of the coating. In addition, the thermal expansion coefficients of the FeAl phase and the Fe2Al5 phase are between those of stainless steel and alumina ceramics. As a transition layer, they can play a transitional role between the two, making the thermal expansion process more coordinated and reducing the thermal stress caused by thermal expansion mismatch.
[0030] (5) The aluminum oxide layer of the present invention includes both α-Al2O3 phase and γ-Al2O3 phase. The coating formed by the mixture of the two can have both certain toughness and high hardness. It can withstand a certain degree of deformation without breaking, and can firmly adhere to the stainless steel substrate without peeling off, thereby improving the reliability and stability of the coating.
[0031] (6) The method of the present invention is very environmentally friendly. The deposition liquid does not pollute the environment. No pollutants are produced during the entire process. The hydrogen generated during the electrophoretic deposition process is of high purity and contains no other impurity gases, making it easy to collect and utilize. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The SEM image (a) and BSE image (b) of the interface of the stainless steel material containing Al2O3 coating prepared in Example 1 of the present invention.
[0033] Figure 2 This is the XRD pattern of the aluminum oxide layer of the stainless steel material containing the Al2O3 coating prepared in Example 1 of the present invention.
[0034] Figure 3 This is a SEM image of the cross section of the stainless steel material after heat treatment in Example 1 of the present invention.
[0035] Figure 4 This is a SEM image of the cross section of the stainless steel material of Comparative Example 1 of the present invention after no heat treatment.
[0036] Figure 5 This is a cross-sectional EDS point scanning diagram of the stainless steel material containing Al2O3 coating after high-temperature oxidation in Example 1 of the present invention.
[0037] Figure 6 This is a graph showing the effect of different polyvinyl butyral contents on the deposition amount in Example 5 of the present invention.
[0038] Figure 7 This is a graph showing the effect of different aluminum nitrate nonahydrate contents on the deposition amount in Example 6 of the present invention.
[0039] Figure 8 This is a physical picture of the stainless steel material with a single Al2O3 coating after heat treatment in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.
[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0042] Example 1
[0043] This embodiment provides a method for preparing a stainless steel material containing an Al2O3 coating, comprising the following steps:
[0044] 1. Preprocessing
[0045] The 316L stainless steel was polished step by step on 120#, 240#, 400#, and 600# silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.
[0046] 2. Preparation of electrophoretic deposition solution
[0047] While maintaining magnetic stirring, 6 g of aluminum nitrate nonahydrate powder (calculated as aluminum nitrate), 10 g of metal aluminum powder and 4 g of polyvinyl butyral were added to 100 mL of ethanol in proportion, followed by magnetic stirring for 30 min and ultrasonic dispersion for 30 min to obtain an electrophoretic deposition solution.
[0048] 3. Electrophoretic deposition aluminum plating
[0049] Stainless steel and graphite were immersed in the deposition solution, with stainless steel as the cathode and graphite as the anode. The deposition voltage was 100 V, the deposition time was 5 min, the distance between the electrodes was 2 cm, and magnetic stirring was maintained during the process.
[0050] 4. Heat treatment and high temperature oxidation
[0051] After drying, it was placed in a tubular furnace, and after passing argon, the temperature was increased to 700°C at 5°C / min and kept at this temperature for 2 hours. Then, air was passed and the temperature was increased to 900°C at 2°C / min and kept at this temperature for 10 hours. Subsequently, the material was cooled to room temperature with the furnace to obtain a stainless steel material containing an Al2O3 coating.
[0052] Figure 1 (a) and Figure 1 (b) are respectively the SEM image (a) and BSE image (b) of the interface of the stainless steel material prepared in this embodiment. It can be seen from the figure that a coating of a certain thickness is formed on the substrate and the stratification is obvious. There is also a transition layer between the substrate and the outermost layer of aluminum oxide, and a metallurgical bond is formed between the coating and the substrate. The thickness of the transition layer is about 15μm, and the thickness of the outermost aluminum oxide layer is about 25μm. In the figure, the transition layer is tightly bonded to the outer layer of aluminum oxide and the boundary is neat and without cracks. The substrate and the transition layer are also tightly bonded, but the boundary between the two is uneven. This is caused by the use of sandpaper to polish the stainless steel substrate during the pretreatment before electrophoretic deposition aluminum plating, and is not generated during the subsequent electrophoretic deposition aluminum plating-heat treatment-high temperature oxidation process. There are some tiny voids between the transition layer and the aluminum oxide layer, which is caused by the mutual diffusion of iron and aluminum atoms between the pure aluminum layer and the substrate at high temperature.
[0053] Depend on Figure 2 It can be seen that the aluminum oxide layer prepared in this embodiment contains both α-Al2O3 phase and γ-Al2O3 phase, and the content of α-Al2O3 phase is greater than that of γ-Al2O3 phase. Figure 5 It can be confirmed that the transition layer of the present invention contains both FeAl phase and Fe2Al5 phase.
[0054] Example 2
[0055] This embodiment provides a method for preparing a stainless steel material containing an Al2O3 coating, comprising the following steps:
[0056] 1. Preprocessing
[0057] The 316L stainless steel was polished step by step on 120#, 240#, 400#, and 600# silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.
[0058] 2. Preparation of electrophoretic deposition solution
[0059] While maintaining magnetic stirring, 12 g of aluminum nitrate nonahydrate powder (calculated as aluminum nitrate), 10 g of metal aluminum powder and 4 g of polyvinyl butyral were added to 100 mL of ethanol in proportion, followed by magnetic stirring for 30 min and ultrasonic dispersion for 30 min to obtain an electrophoretic deposition solution.
[0060] 3. Electrophoretic deposition aluminum plating
[0061] Stainless steel and graphite were immersed in the deposition solution, with stainless steel as the cathode and graphite as the anode. The deposition voltage was 100 V, the deposition time was 5 min, the distance between the electrodes was 2 cm, and magnetic stirring was maintained during the process.
[0062] 4. Heat treatment and high temperature oxidation
[0063] After drying, it was placed in a tubular furnace, and after passing argon, the temperature was increased to 700°C at 5°C / min and kept at this temperature for 2 hours. Then, air was passed and the temperature was increased to 900°C at 2°C / min and kept at this temperature for 10 hours. Subsequently, the material was cooled to room temperature with the furnace to obtain a stainless steel material containing an Al2O3 coating.
[0064] The thickness ratio of the aluminum oxide layer and the transition layer of the stainless steel material containing the Al2O3 coating prepared in this embodiment is 5:3.
[0065] Example 3
[0066] This embodiment provides a method for preparing a stainless steel material containing an Al2O3 coating, comprising the following steps:
[0067] 1. Preprocessing
[0068] The 316L stainless steel was polished step by step on 120#, 240#, 400#, and 600# silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.
[0069] 2. Preparation of electrophoretic deposition solution
[0070] While maintaining magnetic stirring, 6 g of aluminum nitrate nonahydrate powder (calculated as aluminum nitrate), 12 g of metal aluminum powder and 4 g of polyvinyl butyral were added to 100 mL of ethanol in proportion, followed by magnetic stirring for 30 min and ultrasonic dispersion for 30 min to obtain an electrophoretic deposition solution.
[0071] 3. Electrophoretic deposition aluminum plating
[0072] Stainless steel and graphite were immersed in the deposition solution, with stainless steel as the cathode and graphite as the anode. The deposition voltage was 120 V, the deposition time was 10 min, the distance between the electrodes was 2 cm, and magnetic stirring was maintained during the process.
[0073] 4. Heat treatment and high temperature oxidation
[0074] After drying, it was placed in a tubular furnace, and after passing argon, the temperature was increased to 700°C at 5°C / min and kept at this temperature for 2 hours. Then, air was passed and the temperature was increased to 900°C at 2°C / min and kept at this temperature for 10 hours. Subsequently, the material was cooled to room temperature with the furnace to obtain a stainless steel material containing an Al2O3 coating.
[0075] The thickness ratio of the aluminum oxide layer and the transition layer of the stainless steel material containing the Al2O3 coating prepared in this embodiment is 5:3.
[0076] Example 4
[0077] This embodiment provides a method for preparing a stainless steel material containing an Al2O3 coating, comprising the following steps:
[0078] 1. Preprocessing
[0079] The 316L stainless steel was polished step by step on 120#, 240#, 400#, and 600# silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.
[0080] 2. Preparation of electrophoretic deposition solution
[0081] While maintaining magnetic stirring, 6 g of aluminum nitrate nonahydrate powder (calculated as aluminum nitrate), 10 g of metal aluminum powder and 2 g of polyvinyl butyral were added to 100 mL of ethanol in proportion, followed by magnetic stirring for 30 min and ultrasonic dispersion for 30 min to obtain an electrophoretic deposition solution.
[0082] 3. Electrophoretic deposition aluminum plating
[0083] Stainless steel and graphite were immersed in the deposition solution, with stainless steel as the cathode and graphite as the anode. The deposition voltage was 100 V, the deposition time was 5 min, the distance between the electrodes was 2 cm, and magnetic stirring was maintained during the process.
[0084] 4. Heat treatment and high temperature oxidation
[0085] After drying, it was placed in a tubular furnace, and after passing argon, the temperature was increased to 800°C at 5°C / min and kept for 1 hour. Then, air was passed and the temperature was increased to 1050°C at 2°C / min and kept for 10 hours. Subsequently, the material was cooled to room temperature with the furnace to obtain a stainless steel material containing an Al2O3 coating.
[0086] The thickness ratio of the aluminum oxide layer and the transition layer of the stainless steel material containing the Al2O3 coating prepared in the embodiment of the present invention is 5:2.
[0087] The stainless steel materials containing Al2O3 coatings prepared in Examples 1 to 4 and bare 316 stainless steel samples were kept at 1000°C in air for 15 h to examine the oxidation resistance of the samples. The results are shown in Table 1, indicating that the oxidation resistance of the stainless steel materials obtained by the method of the present invention is significantly improved.
[0088] ;
[0089] Example 5
[0090] Under the process parameters of 60 g / L aluminum nitrate nonahydrate content in the electrophoretic deposition solution, 100 g / L metal aluminum powder content, 100 V deposition voltage, 5 min deposition time, and 2 cm plate spacing, the effect of adding 10-45 g / L polyvinyl butyral (1-4.5 g polyvinyl butyral was added to every 100 mL of anhydrous ethanol) on the deposition amount was investigated. The other conditions were the same as in Example 1. The results are shown in FIG. Figure 6 shown.
[0091] The results show that when the content of polyvinyl butyral in the electrophoretic deposition solution is greater than 10g / L (1g of polyvinyl butyral is added to every 100mL of anhydrous ethanol), the coating deposition amount increases significantly. When the content of polyvinyl butyral in the electrophoretic deposition solution is greater than 40g / L, as the content of polyvinyl butyral increases, the deposition amount of aluminum powder begins to decrease, and the uniformity and firmness of the coating deteriorate. Moreover, as polyvinyl butyral is continuously added, the viscosity of the deposition solution also increases. Therefore, it is further preferred that the content of polyvinyl butyral in the deposition solution is 35~40g / L, and further, the content of polyvinyl butyral is 40g / L, which is most suitable.
[0092] Example 6
[0093] Under the process parameters that the content of polyvinyl butyral in the electrophoretic deposition solution is 40 g / L, the content of metal aluminum powder is 100 g / L, the deposition voltage is 100 V, the deposition time is 5 min, and the plate spacing is 2 cm, the effect of the addition amount of aluminum nitrate nonahydrate in the range of 20-160 g / L (2-16 g aluminum nitrate nonahydrate is added to every 100 mL of anhydrous ethanol) on the deposition amount is investigated. The other conditions are the same as in Example 1. The results are as follows: Figure 7 shown.
[0094] The results show that when other process conditions remain unchanged, the deposition amount will increase with the increase of aluminum nitrate nonahydrate content. However, when the aluminum nitrate nonahydrate content exceeds 120g / L, the deposition amount will decrease. The aluminum nitrate nonahydrate content will directly affect the conductivity of the electrophoretic deposition solution. When the conductivity is too large, the deposition current will be too large, which will bring some adverse effects. First, excessive deposition current will cause a large number of bubbles to be generated on the cathode, which is not conducive to the formation of aluminum coating, and will also destroy the uniformity of the aluminum coating, causing the deposition amount to decrease. Secondly, excessive deposition current will also cause the temperature of the electrophoretic deposition solution to rise rapidly, seriously affecting the formation of the aluminum coating. Therefore, the content of aluminum nitrate nonahydrate in the electrophoretic deposition solution is further preferably 100~120g / L.
[0095] Example 7
[0096] This example investigates the effect of high temperature oxidation treatment time of 5 to 25 hours on the hardness of the aluminum oxide layer and the transition layer. The remaining conditions and steps are consistent with those in Example 1. The results are shown in Table 2.
[0097] ;
[0098] At the same time, the wear resistance of the coating was tested by SRVⅢ reciprocating friction and wear tester on the samples of stainless steel materials containing Al2O3 coating prepared at different high temperature oxidation treatment times. The results are shown in Table 3.
[0099] ; The wear resistance of the sample with a high-temperature oxidation time of 5h is the worst. This is because in the early stage of oxidation, a layer of γ-Al2O3 film and some α-Al2O3 particles are formed on the surface of the metal aluminum layer, but at this time the γ-Al2O3 film is thin and the α-Al2O3 particles are small. As the high-temperature oxidation treatment time increases, the thickness of the aluminum oxide layer continues to increase and the α-Al2O3 in the aluminum oxide layer increases. The hardness of the aluminum oxide layer also increases, and the wear resistance of the coating becomes better and better. However, after the high-temperature oxidation treatment time exceeds 20h, the oxidation time is too long, which will cause local overheating of the film layer, generate internal stress, and easily cause local microcracks, resulting in a slight decrease in the wear resistance of the coating.
[0100] Comparative Example 1
[0101] The only difference compared with Example 1 is that no heat treatment is performed in argon (direct high-temperature oxidation after electrophoretic deposition of aluminum), and the remaining steps and conditions are the same to obtain a stainless steel material.
[0102] The cross section of the stainless steel material of Comparative Example 1 is as follows Figure 4 As shown, and Figure 3 In contrast, direct high-temperature oxidation without heat treatment will cause the aluminum oxide coating to break.
[0103] Comparative Example 2
[0104] A method for preparing a stainless steel material with a single Al2O3 coating directly using aluminum sol electrophoretic deposition comprises the following steps:
[0105] 1. Preprocessing
[0106] The 316L stainless steel was polished step by step on 120#, 240#, 400#, and 600# silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.
[0107] 2. Preparation of electrophoretic deposition solution
[0108] Under the condition of water bath temperature of 85℃ and magnetic stirring, ASB (aluminum sec-butoxide) was slowly added to deionized water. After magnetic stirring, HNO3 was added (the molar ratio of deionized water, aluminum sec-butoxide, and HNO3 was: deionized water: aluminum sec-butoxide: HNO3 = 90:1:0.2 molar ratio). Then magnetic stirring was performed for 2h and ultrasonic dispersion was performed for 30min to obtain a stable aluminum sol. Subsequently, 40mL of anhydrous ethanol was added to 60mL of aluminum sol, and 3g of nano-alumina powder was added under continuous stirring. After magnetic stirring for 30min, ultrasonic vibration was performed for 30min.
[0109] 3. Electrophoretic deposition aluminum plating
[0110] Stainless steel and graphite were immersed in the deposition solution, with stainless steel as the cathode and graphite as the anode. The deposition voltage was 4V, the deposition time was 3min, the distance between the electrodes was 2cm, and magnetic stirring was maintained during the process.
[0111] 4. Heat treatment
[0112] After drying, the tube furnace was placed, and argon was introduced and the temperature was raised to 700°C at 5°C / min and kept at this temperature for 2h. Then the tube furnace was taken out and exposed to the air to obtain a stainless steel material with a single Al2O3 coating. Figure 8 As shown, the single aluminum oxide coating cracked and fell off.
Claims
1. A stainless steel material containing Al2O3 coating, characterized in that: It comprises a stainless steel substrate, a transition layer and an aluminum oxide layer, wherein the stainless steel substrate and the aluminum oxide layer are connected via the transition layer; The transition layer includes FeAl phase and Fe2Al5 phase; The aluminum oxide layer includes an α-Al2O3 phase and a γ-Al2O3 phase, and the content of the α-Al2O3 phase is greater than the content of the γ-Al2O3 phase; The thickness ratio of the aluminum oxide layer to the transition layer is (1-5):(2-7).
2. The stainless steel material containing Al2O3 coating according to claim 1, characterized in that: The stainless steel matrix contains Fe and at least one element of Cr, Ni, Mo, Mn, and Ti.
3. The method for preparing a stainless steel material containing an Al2O3 coating according to claim 1 or 2, characterized in that: Aluminum is plated on the surface of a stainless steel substrate by electrophoretic deposition to deposit a powdered aluminum coating, which is then heat treated in an inert gas to form a molten aluminum powder layer, and then oxidized at high temperature to obtain the result; The deposition liquid used in the electrophoretic deposition aluminum plating comprises metal aluminum powder, polyvinyl butyral, aluminum nitrate and / or aluminum nitrate hydrate and anhydrous ethanol.
4. The method for preparing a stainless steel material containing an Al2O3 coating according to claim 3, characterized in that: The content of the metal aluminum powder in the deposition liquid is 80-120 g / L, the content of polyvinyl butyral is 10-45 g / L, and the content of aluminum nitrate and / or aluminum nitrate hydrate is 60-140 g / L in terms of aluminum nitrate.
5. The method for preparing a stainless steel material containing an Al2O3 coating according to claim 4, characterized in that: The conditions for electrophoretic deposition aluminum plating are: the stainless steel substrate is used as the negative electrode, the graphite is used as the positive electrode, the deposition voltage is 80-120V, and the deposition time is 5-10min.
6. The method for preparing a stainless steel material containing an Al2O3 coating according to claim 4 or 5, characterized in that: The heat treatment conditions are: heating to 700-800° C. at a rate of 5-10° C. / min in an argon atmosphere and keeping the temperature for 1-3 hours.
7. The method for preparing a stainless steel material containing an Al2O3 coating according to claim 6, characterized in that: The high temperature oxidation conditions are: heating to 900-1050° C. at 1-5° C. / min in an oxidizing atmosphere, keeping the temperature for 5-25 hours, and then cooling to room temperature in the furnace.
Citation Information
Patent Citations
High temperature oxidation resistant NiAl-Y2O3 coating, its preparation method and its application
CN102776546A
Preparation method of high-temperature wear-resistant coating on surface of steel piece
CN103628013A
Nano-zirconia thermal barrier coating material on stainless steel surface, and preparation process thereof
CN106702303A
Liquid metal lead bismuth corrosion resistant coating and preparation method thereof
CN117051453A
Method for preparing nanometer aluminum oxide coating on surface of 310S stainless steel
CN119243116A